Reliability Analysis of Tailings Storage Facility Embankments: Investigating the Effect of Zonation on Slope Stability - Bamisaye, Rapheal Temitayo (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.